The Complex Puzzle of Hypertrophic Phenotype - Felix, Alex Dos Santos (2025)
Left ventricular hypertrophy (LVH) represents a frequent observation in clinical practice. Nonetheless, the hypertrophic phenotype emerges as a common manifestation of diverse conditions, thereby presenting a diagnostic conundrum for clinicians. Differentiation among the etiologies of LVH is imperative for therapy decision-making, as different approaches must be implemented for distinct conditions, such as LVH secondary to loading changes, hypertrophic cardiomyopathy (HCM), or HCM mimics. In some instances, an erroneous or late diagnosis may lead to a progression of the underlying disease with worsening functional capacity, high morbidity and mortality. The rational use of cardiovascular multimodality imaging is of great importance when carried out in addition to a thorough clinical assessment and correlated with electrocardiographic findings, providing clues to fill the gaps, being, most of the time, the missing piece to solve this challenging puzzle. An integrative approach is of paramount importance for the evaluation of these patients, as they are often followed by several specialties, with varied systemic manifestations. Although a multidisciplinary team is needed for an optimized follow-up of these patients, the most important player in this journey is the clinician, whose mission is to bring together all the red flags and coordinate all the data for an assertive diagnosis. The objective of this review is to provide a pragmatic methodology, highlighting important clues for discriminating among the diverse conditions that result in LVH.